Meaning of nouns : semantic theory in classical and medieval India : Nāmārtha-nirṇaya of Kauṇḍabhaṭṭa - Kauṇḍabhaṭṭa (D.K. Printworld, 2007)
Work on Sanskrit noun and sementics; Sanskrit text with study and translation.